Self-Compassion and Subjective Well-Being Mediate the Impact of Mindfulness on Balanced Time Perspective in Chinese College Students - Ge, Jingjing; Wu, Jun; Li, Kesheng; Zheng, Yong (Frontiers in Psychology, 2019)
Balanced time perspective is associated with optimal social functioning and facilitates adaptation to pressure and changes in the environment. Previous studies have found that mindfulness is positively associated with and might promote balanced time perspective. However, the mechanism through which mindfulness affects balanced time perspective remains unexplored. The purpose of the present study was to investigate the mediating role of self-compassion and subjective well-being in the relationship between mindfulness and balanced time perspective. A total of 754 Chinese college students, aged 17–27 years, completed the Chinese versions of the Five-Facet Mindfulness Questionnaire, Self-Compassion Scale, Subjective Well-Being Scale, and Zimbardo Time Perspective Inventory. There were significant positive correlations between mindfulness, self-compassion, subjective well-being, and balanced time perspective. Structural equation modeling indicated that in addition to the direct influence of mindfulness on balanced time perspective, self-compassion and subjective well-being played a partial mediating role. On the basis of these findings, we conclude that mindfulness has an important positive influence on balanced time perspective, and highlight the crucial role of the self-compassion in cultivating an individual's balanced time perspective. Limitations of the present study are also discussed.